RETRACTED: Curcumin-Free Turmeric Exhibits Activity against Human HCT-116 Colon Tumor Xenograft: Comparison with Curcumin and Whole Turmeric - Prasad, Sahdeo; Tyagi, Amit K.; Siddik, Zahid H.; Aggarwal, Bharat B. (Frontiers in Pharmacology, 2017)
Extensive research within last two decades has indicated that curcumin extracted from turmeric (Curcuma longa), exhibits anticancer potential, in part through the modulation of inflammatory pathways. However, the residual antitumor activity of curcumin-free turmeric (CFT) relative to curcumin or turmeric is not well understood. In the present study, therefore, we determined activities of these agents in both in vitro and in vivo models of human HCT-116 colorectal cancer (CRC). When examined in an in vitro antiproliferative, clonogenic or anti-inflammatory assay system, we found that curcumin was highly active whereas turmeric and CFT had relatively poor activity against CRC cells. However, when examined in vivo at an oral dose of either 100 mg/kg or 500 mg/kg given to nude mice bearing CRC xenografts, all three preparations of curcumin, turmeric and CFT similarly suppressed the growth of the xenograft. The effect of CFT on suppression of tumor growth was dose-dependent, with 500 mg/kg tending to be more effective than 100 mg/kg. Interestingly, 100 mg/kg curcumin or turmeric was found to be more effective than 500 mg/kg. When examined in vivo for the expression of biomarkers associated with cell survival (cIAP-1, Bcl-2, and survivin), proliferation (Ki-67 and cyclin D1) and metastasis (ICAM-1 and VEGF), all were down-modulated. These agents also suppressed inflammatory transcription factors (NF-κB and STAT3) in tumor cells. Overall, our results with CFT provide evidence that turmeric must contain additional bioactive compounds other than curcumin that, in contrast to curcumin, exhibit greater anticancer potential in vivo than in vitro against human CRC. Moreover, our study highlights the fact that the beneficial effects of turmeric and curcumin in humans may be more effectively realized at lower doses, whereas CFT could be given at higher doses without loss in favorable activity.